ORGANIZACIÓN CONTABLE Y ANÁLISIS FINANCIERO EN EL AUTOSERVICIO MERCATONE DE LA CIUDAD DE LOJA, DURANTE EL PERIODO ENERO-MARZO DEL 2014 - Reinoso Patiño, Johanna Maricela (2016)
This thesis entitled "ACCOUNTING AND ORGANIZATION FINANCIAL ANALYSIS ON SELF MERCATONE of the city of Loja, during the period January-March 2014" was constructed on the basis of the general rules for graduation issued by the National University of Loja, as a prerequisite to obtaining of Engineering degree in Accounting and Auditing requirement. In order to comply with the goals outlined in this thesis, plan and manual accounts that are used for the development of the accounting process was developed; inventory of goods was effected in physical form, noting the presence of existing products for sale; the accounting process was carried out, building and auxiliary accounting records according to the needs of AUTOSERVICIO MERCATONE who admitted establish its development from the initial inventory, to the financial statements, which reflect the results obtained in this period; control of bank book was formalized, then to check the records of our bank book matched the bank's records performing bank reconciliation; VAT Declaration was made in the form 104; the months of January, February and March 2014, making clear the values that the company must pay SRI, and keep up to date with their tax obligations. He introduced himself and the financial statements are analyzed, through financial analysis and indicators to assess the Financial, Economic and Operational Business performance to facilitate decision-